Code-switching in Second Language Acquisition: A Systematic Literature Review on Benefits and Challenges - Lauta, Lyn C.; Estremera, Michael (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This systematic literature review provides a comprehensive examination of the multifaceted role of Code-Switching (CS) in the complex process of Second Language Acquisition (SLA). This study includes a systematic literature review following the PRISMA model to identify, screen, and analyze relevant research on CS in education, ensuring a comprehensive and transparent selection of high-quality sources. The articles analyzed met the inclusion criteria: empirical works, under the theme of CS in SLA, language learners as the research subject, and elaborating benefits and challenges of CS. Of 850 screened records, 50 articles were qualitatively synthesized, making up the systematic review material. The findings of this review reveal that CS can serve as a valuable and versatile strategy for learners, enabling them to overcome temporary linguistic limitations, enhance comprehension of complex concepts, and actively participate in communication even when faced with gaps in their target language proficiency. It highlights how CS can facilitate meaning negotiation, foster a sense of belonging, and promote a more comfortable and inclusive learning atmosphere. However, the review also acknowledges and thoroughly analyzes potential drawbacks associated with CS, such as the risk of over-reliance on the first language (L1), which may inadvertently impede the development of target language proficiency and hinder the acquisition of necessary linguistic resources. This includes the potential for fossilization of errors and the avoidance of challenging target language structure. This study implies that while CS can be a prevailing communicative and pedagogical means in SLA, its use must be thoughtful to avoid undesirable effects. Therefore, schools and stakeholders could implement strategic actions to effectively equip teachers to use CS within diverse educational contexts.